Pengaruh Permainan Menjahit terhadap Kemampuan Motorik Halus Anak 5-6 Tahun - Wahyuni, Juherni; Mayar, Farida; Zulminiati, Zulminiati (Penerbit Aksara Rentaka Siar (ARS), 2019)
The purpose of this study was to determine the fine motoric abilities of children 5-6 years old through sewing games at the Yayasan Wanita Kereta Api kindergarten in Padang. Fine motor learning activities in that school use several activities such as thickening letters, drawing and colouring. So that it only develops on the fingers of a child. To find out the fine motoric abilities of children 5-6 years old this study used sewing games. Quasy Experimental is the approach of this study with a research population totaling 20 children. The control class is B2 sample and experimental class B1 sample and amounted to 10 children each class with purposive sampling technique of this study and data collection techniques using action tests and data collection tools used statement sheets then the data is processed by a difference test (t-test). the results showed the average value of the control class was 70.62 and the experimental class was 79.37. Then it can be concluded that the use of sewing games has a significant effect on the fine motor skills of children 5-6 years in Yayasan Wanita Kereta Api kindergarten in Padang Academic Year 2018/2019.